2018
DOI: 10.1080/02699206.2018.1459852
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual English-Mandarin-Malay phonological error patterns: An initial cross-sectional study of 2 to 4 years old Malaysian Chinese children

Abstract: Child multilingual phonological errors are under-explored. Cross-linguistic studies suggest monolingual children make phonological errors that are subject to effects of language universality and ambient language characteristics. Bilingual Chinese children were observed to use not only typical, but also atypical phonological errors compared to monolingual peers acquiring similar languages. Atypical errors are a result of specific bilingual pair effects. Close-language-relatedness (Cantonese-Mandarin) is claimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…In addition, for the pitch contour inspected via spectrograms, it was observed that Tone 3 and Tone 4 are carrying a similar falling contour shape. This finding is consistent with previous studies (Lim et al 2015;Lim 2018) demonstrating that the pitch contour for Tone 3 is mid-low to low (2-1) for the Malaysian Mandarin (Maldarin), rather than mid-low, low to midhigh (2-1-4) for the Chinese Putonghua. Regardless of this similarity in terms of pitch contour, the Tone 3 word tokens with such pitch contours were acceptable and not discarded.…”
Section: Phase Ii: Development Of Digitized Word Tokens and Suitabilisupporting
confidence: 93%
“…In addition, for the pitch contour inspected via spectrograms, it was observed that Tone 3 and Tone 4 are carrying a similar falling contour shape. This finding is consistent with previous studies (Lim et al 2015;Lim 2018) demonstrating that the pitch contour for Tone 3 is mid-low to low (2-1) for the Malaysian Mandarin (Maldarin), rather than mid-low, low to midhigh (2-1-4) for the Chinese Putonghua. Regardless of this similarity in terms of pitch contour, the Tone 3 word tokens with such pitch contours were acceptable and not discarded.…”
Section: Phase Ii: Development Of Digitized Word Tokens and Suitabilisupporting
confidence: 93%
“…Developmental or typical phonological patterns (i.e., natural phonological processes), which are observed in more than 10% of a peer group, become gradually inhibited with age and constitute a sign of the maturity of the phonological system. Phonological patterns that occur in less than 10% of the peer group and are not inhibited with development are defined as atypical (Lim, 2018;Preston et al, 2013). Nondevelopmental or atypical phonological patterns are a sign of a phonological disorder.…”
Section: Phonological Patternsmentioning
confidence: 99%
“…Nondevelopmental or atypical phonological patterns are a sign of a phonological disorder. However, substantial variation has been observed in the categorization of phonological patterns across studies (Jeng, 2011;Lim, 2018;Xin Xin & To, 2017).…”
Section: Phonological Patternsmentioning
confidence: 99%
“…Kebanyakan kajian yang dilaksanakan ke atas penutur Cina adalah untuk meneliti masalah pembelajaran yang dihadapi dan kadar kesalahan yang dilakukan dalam proses mempelajari bahasa Melayu sebagai bahasa kedua dari segi penulisan (Chew Fong Peng, 2016;Norsimah Mat Awal et al, 2012) dan sebutan (Lim Hui Woan & Lim Su Hui, 2017). Kajian mengenai kadar pemerolehan fonologi dan pola kesalahan kanak-kanak pelbagai bahasa Bahasa Inggeris-Mandarin-Bahasa Melayu (Lim, 2018;Lim et al, 2015) juga sudah dijalankan di Malaysia. Namun begitu, data mengenai kontras suara bahasaMandarin dalam bahasa Melayu masih kurang dikaji.…”
Section: Abstrakunclassified